I want a better catastrophe : navigating the climate crisis with grief, hope, and gallows humor : an existential manual for tragic optimists, can-do pessimists, and compassionate doomers! - Boyd, Andrew, 1962- (Gabriola Island, BC, Canada : New Society Publishers, 2023)
"Reeling from a crisis of hope, lifelong activist Andrew Boyd seeks out today's leading climate thinkers, from collapse-psychologist Jamey Hecht to Indigenous botanist Robin Wall Kimmerer. "If it's the end of the world, now what?" he asks, as he steers us through our climate angst in search of a "better catastrophe.""--
Prologue: it's the end of the world, now what? -- Impossible news -- The five stages of climate grief -- Existential crisis scenario planning -- How to be white at the end of the world -- Is there hope? -- What is still worth doing? -- Experiments on the verge -- Another end of the world is possible -- Epilogue: now is when you are needed most -- Epi-epilogue: passing the torch -- Appendix: stuff you can (still) do.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Climatic changes; Climate change mitigation; Sustainable living; Human ecology; Anxiety; Climat -- Changements; Climat -- Changements -- Atténuation.; Style de vie durable; Écologie humaine; climate change; human ecology; Climate change mitigation; Climatic changes; Human ecology; Sustainable living